Templating Functional Materials Using Self-Assembled Block Copolymer Thin-Film for Nanodevices - Subramanian, Ashwanth; Tiwale, Nikhil; Lee, Won-Il; Nam, Chang-Yong (Frontiers in Nanotechnology, 2021)
The nanometer-scale architectures in thin films of self-assembling block copolymers (BCPs) have inspired a variety of new applications, specifically in fabrication of nanodevices, which offer various advantages, such as, small device footprint, low operational power and enhanced device performance. Imperative for this application, however, is the ability to transform these small polymeric patterns into useful inorganic structures. BCP-templated inorganic nanostructures have shown the potential for use as an active material in various electronic device applications, including, field-effect transistors, photodetectors, gas sensors and many more. This article reviews the various strategies that have been implemented in the past decade to fabricate devices at nanoscale using block copolymer thin films.